2016
DOI: 10.1016/j.scitotenv.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylarsinic acid contaminated soil remediation by titanium dioxide (P25) photocatalysis: Degradation pathway, optimization of operating parameters and effects of soil properties

Abstract: Diphenylarsinic acid (DPAA) is formed during the leakage of arsenic chemical weapons in sites and poses a high risk to biota. However, remediation methods for DPAA contaminated soils are rare. Here, the photocatalytic oxidation (PCO) process by nano-sized titanium dioxide (TiO 2 ) was applied to degrade DPAA in soil. The degradation pathway was firstly studied, and arsenate was identified as the final product. Then, an orthogonal array experimental design of L 9 (3) 4 , only 9 experiments were needed, instead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…It has also been observed that all the parameters mentioned above result in the removal efficacy of 82.7% of the DPAA. It has been reported that the DPAA is not completely converted by TiO 2 NPs, rather its inorganic arsenic products are adsorbed by these NPs, hence playing crucial role in eradicating DPAA pollution [ 126 ].…”
Section: Tio 2 Nps In Environmental Remediationmentioning
confidence: 99%
“…It has also been observed that all the parameters mentioned above result in the removal efficacy of 82.7% of the DPAA. It has been reported that the DPAA is not completely converted by TiO 2 NPs, rather its inorganic arsenic products are adsorbed by these NPs, hence playing crucial role in eradicating DPAA pollution [ 126 ].…”
Section: Tio 2 Nps In Environmental Remediationmentioning
confidence: 99%
“…In addition, using artificial solar light on the photocatalytic process can be efficient. In another study, Wang et al (2016a) investigated the photocatalytic oxidation pathway of diphenylarsinic acid (DPAA) contaminated soil by nano-sized titanium dioxide (TiO2).…”
Section: Photocatalysismentioning
confidence: 99%
“…Unfortunately, the limited-application of TiO 2 is due to its large band gap (3.2 eV) and low quantum yield in visible light region. [8,[18][19] Compared with TiO 2 , ZnO has been proposed as the promising photocatalyst to replace TiO 2 because of its same band gap energy, but shows higher absorption efficiency of the solar spectrum, special optical, strong oxidation activity and electrical properties and low electron affinity. Thus, it has drawn dominant interests in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of photodegradation of organic pollutants primarily depends on the adsorbability for the pollutant and the quantum efficiency of the catalyst. Unfortunately, the limited‐application of TiO 2 is due to its large band gap (3.2 eV) and low quantum yield in visible light region [8,18–19] . Compared with TiO 2 , ZnO has been proposed as the promising photocatalyst to replace TiO 2 because of its same band gap energy, but shows higher absorption efficiency of the solar spectrum, special optical, strong oxidation activity and electrical properties and low electron affinity.…”
Section: Introductionmentioning
confidence: 99%